TERT promoter mutation and its interaction with IDH mutations in glioma: Combined TERT promoter and IDH mutations stratifies lower-grade glioma into distinct survival subgroups—A meta-analysis of aggregate data. (December 2017) - Vuong, Huy Gia; Altibi, Ahmed M.A.; Duong, Uyen N.P.; Ngo, Hanh T.T.; Pham, Thong Quang; Chan, Aden Ka-Yin; Park, Chul-Kee; Fung, Kar-Ming; Hassell, Lewis
Highlights: TERT promoter mutations are common in gliomas. The prognostic values of TERT promoter mutations in gliomas are dependent on tumor grade and IDH mutational status. The combination of TERT and IDH mutations helps stratify WHO grade II/III gliomas into distinct survival subgroups. Abstract: The clinical significance of telomerase reverse transcriptase ( TERT) promoter mutation in glioma remains unclear. The aim of our meta-analysis is to investigate the prognostic impact TERT promoter mutation in glioma patients and its interaction with other molecular markers, particularly Isocitrate Dehydrogenase (IDH) mutation from aggregate level data. Relevant articles were searched in four electronic databases including PubMed, Scopus, Web of Science and Virtual Health Library. Pooled HRs were calculated using random effect model weighted by inverse variance method. From 1010 studies, we finally included 28 studies with 11519 patients for meta-analyses. TERT mutation is significantly associated with compromised overall survival (OS) (HR = 1.38; 95% CI = 1.15–1.67) and progression-free survival (PFS) (HR = 1.31; 95% CI = 1.06–1.63) in glioma patients. In studying its reaction with IDH, TERT promoter mutation was associated with reduced OS in both IDH -mutant ( IDH- mut) and IDH -wild type ( IDH- wt) glioblastomas but shown to have inverse effects on IDH- mut and IDH- wt grade II/III tumors. Our analysis categorized WHO grade II/III glioma patients into four distinct survival subgroups with descending survival as follow: TERT- mut/ IDH- mut ≫  TERT- wt/ IDH- mut ≫  TERT- wt/ IDH- wt ≫  TERT- mut/ IDH- wt. Prognostic value of TERT promoter mutations in gliomas is dependent on tumor grade and the IDH mutational status. With the same tumor grade in WHO grade II and III tumors and the same IDH mutation status, TERT-mut is a prognostic factor.